How to measure growth? (Cultura Económica, 2019)
When analyzing the current state of the Argentine economy, politicians, journalists and economists use GDP growth as the main and sometimes most important variable to keep in mind. While that is correct in a first analysis, to remain in that primary level is consideredshortsighted by the author. Researchers such as Bourguignon (2004) have shown that a somewhat more comprehensive approach to analyzing the effectiveness of GDP growth in a society is to consider jointly the level of income inequality and poverty levels of society. According to the author, the growth of income, like income inequality and poverty levels of society are closely related.
Keywords: GDP growth; poverty; income inequality; internal distribution